A routing underlay for overlay networks. - Nakao, Akihiro
We argue that designing overlay services to independently probe the Internet--with the goal of making informed application-specific routing decisions--is an untenable strategy. Instead, we propose a shared routing underlay that overlay services query. We posit that this underlay must adhere to two high-level principles. First, it must take cost (in terms of network probes) into account. Second, it must be layered so that specialized routing services can be built from a set of basic primitives. These principles lead to an underlay design where lower layers expose large-scale, coarse-grained static information already collected by the network, and upper layers perform more frequent probes over a narrow set of nodes. This paper proposes a set of primitive operations and three library routing services that can be built on top of them, and describes how such libraries could be useful to overlay services.
Keywords: Computer systems organization; Computer communication networks; Algorithms; Design; Infrastructure; Overlay networks; Routing